The Israeli-Syrian Peace Talks: 1991-1996 and Beyond by Helena Cobban (Washington, DC: Un ited States Institute of Peace, 1999. 235 pages.) (American Journal of Islam and Society, 2002)
According to Uri Savir, one of the two Israeli chief negotiators who ledtheir country's team to the Israeli-Syrian talks in Washington, DC, in the1990s, "there was a sense among both delegations that, if necessary, wecould go on living without peace." This sense of a fallback position,engendered mainly by the absence of any urgent existential need to reacha final settlement, is what distinguishes these talks from the IsraeliPalestiniannegotiations whose failure is fraught with many risks andunforeseen consequences.Cobban's book draws on research she conducted for her 1991 book,The Super-Powers and the Syrian-Israeli Conflict, and her 1997 monograph,Syria and the Peace: A Good Chance Missed Published and partlyfunded by the United States Institute of Peace, a federal institution createdby Congress in 1984 to promote research on the peaceful managementand resolution of international conflicts, the volume consists ofeight chapters, supplemented with a forward by the president of theInstitute, Richard Solomon, and a thirty-page section devoted to notes.The book contains no illustrations, photographs, appendices, or bibliographicinformation; however, it does offer a small map of Syria andIsrael at the beginning of the book and an eight-page index section at theend.Although somewhat overshadowed by the off-again-on-again IsraeliPalestiniantalks during the 1990s, the Israeli-Syrian negotiations (propelled initially by the 1991 Madrid Peace conference) lasted a period of 52months and, to varying degrees of enthusiasm and success, engaged threesuccessive Israeli governments. The author offers a fascinating account of ...